2020
DOI: 10.36085/agrotek.v14i2.1033
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PEMBERIAN PUPUK KANDANG SAPI DAN PUPUK TSP TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays saccharata L.)

Abstract: Jagung manis (Zea mays saccharata L.) merupakan salah satu jenis tanaman jagung yang belum lama dikenal dan berkembang di Indonesia. Salah satu faktor yang menjadi kendala dalam pengembangan jagung manis karena keterbatasan lahan produktif, dan fungsinya telah berubah. Sebagai upaya peningkatan produksi jagung manis pada umumnya terkendala oleh lahan yang tidak subur dan petani harus mampu memanfaatkan lahan yang tidak subur untuk mencapai hasil yang maksimal, misalnya penggunaan pupuk sapi dan TSP. Penelitian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…Pratama et al (2014) reported that cattle bone ash could increase pH, soil available P, plant P uptake, plant height, plant crown dry weight, and plant root dry weight. These finding align with the results of Utami (2016), stating that using nano cattle bone ash as a source of phosphorus effectively replaces SP-36 in sweet corn cultivation.…”
Section: Plant Growthsupporting
confidence: 89%
See 1 more Smart Citation
“…Pratama et al (2014) reported that cattle bone ash could increase pH, soil available P, plant P uptake, plant height, plant crown dry weight, and plant root dry weight. These finding align with the results of Utami (2016), stating that using nano cattle bone ash as a source of phosphorus effectively replaces SP-36 in sweet corn cultivation.…”
Section: Plant Growthsupporting
confidence: 89%
“…P element has a role in bulb formation and smooth carbohydrate metabolism (Tekeste et al, 2018). This is in line with Utami (2016), stating that using nano cattle bone ash as a source of phosphorus effectively results in replacing SP-36 in sweet corn cultivation. Similarly, Sekarsari (2020) reported that applying OPEFB nano fertilizer with the foliar method resulted in the highest average fresh weight of shallot bulbs per clump.…”
Section: Yield Of Shallotsupporting
confidence: 60%
“…Figure 7 shows that the application of organic and inorganic fertilizers can increase the height of corn plants even though there were no significant differences between treatments. These results are in line with Suprianto et al (2016), stating that the application of a combination of chicken manure with NPK did not have a significant effect on the height of sweet corn plants. This is presumably because the corn plants have reached maximum growth, hence, the further addition of fertilizer doses can not significantly increase their height.…”
Section: Plant Heightsupporting
confidence: 89%
“…Konsentrasi pupuk NPK dan POC D'NIP dalam penelitian ini masih belum optimal untuk memberikan suplai unsur N yang berperan untuk pembentukan jumlah helai daun. Menurut (Cesasna, 2020;Hayati, Prihastanti, & Hastuti, 2019;Mahdiannorr et al, 2016)menyatakan bahwa proses pembentukan daun tidak terlepas dari peranan unsur hara seperti nitrogen dan fosfor yang tersedia bagi tanaman. Kedua unsur hara ini berperan dalam pembentukan sel -sel baru dan komponen utama penyusun senyawa organik dalam tanaman yang mempengaruhi pertumbuhan vegetatif tanaman, khususnya peningkatan jumlah daun.…”
Section: Jumlah Daun (Helai)unclassified